Federal Republic of Yugoslavia : Request for a Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The new government of the Federal Republic of Yugoslavia has formulated and started to implement an ambitious program of stabilization and reform with impressive speed and commitment. The program provides for macroeconomic policies designed to reduce inflation and support reconstruction coupled with bold reforms. The policy achievements so far have been impressive. Prudent policies alone cannot ensure progress toward sustainable growth and external viability. The program sets the basis for the country in achieving sustainable output growth and a viable external position.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet